BIOSCREENING FOR HYPOGLYCEMIC POTENTIAL OF AQUEOUS EXTRACT OF Tridax procumbens IN MICE MODEL - Njangiru, Isaac Kinyua; N, 2NJAGI, E.M.; N, 3NGERANWA, J.J. (Jour Med Resh and Health Sci, 2019)
Tridax procumbens has been used in the treatment of several ailments in Kenya, including diabetes mellitus. However, there is limited scientific validation of its efficacy. The aim of this study was to investigate, in vivo, hypoglycemic activity of Tridax procumbens in alloxan induced diabetic mice. Antidiabetic activity was assessed by administering orally and intraperitoneally aqueous plants extract at doses of 50, 100, 200 and 300mg/kg body weight and determining the levels of blood glucose after 0, 1, 2, 3, 4, 6 and 24 hours. The mineral composition of the aqueous plant extract was assayed, using Total Reflection X-ray Fluorescence system (TRXF), while the phytochemicals were profiled using standard procedures. The plant extract demonstrated a dose independent antidiabetic activity in mice model. The studied plant extract contained alkaloids, flavonoids, saponins, tannins, and total phenols at varying concentration. The mineral assay confirmed the presence of detectable levels of K, Ca, Ti, V, Mn, Fe, Ni, Cu, Zn and As. The aqueous extract of the studied plant was effective in lowering blood glucose levels.